Four new species of Cephennomicrus Reitter (Coleoptera, Staphylinidae, Scydmaeninae) from Malaysia - Jałoszyński, Paweł (Zootaxa, 2015)
Four new species of Cephennomicrus are described from Malaysia: C. curvidens sp. n., C. gentingensis sp. n. (both from the Genting Highlands, West Malaysia), C. santubongensis sp. n. and C. muluensis sp. n. (both from Sarawak, East Malaysia). Male genitalia of all new taxa are illustrated and diagnostic characters are discussed.